Biosecurity: Awareness and Its Significance - Angas, Jibril Aldrich T.; Bonilla, Llyhan D.; Ferre, Ernest Jhon; Ondras, Erl Brian B.; Malaco, Amera; Besa, Adonis (Universitas Pendidikan Indonesia (UPI), 2021)
This study was purposely made to assess biosecurity, or the management of risks to health, economy, industry, and environment. The consequences are caused by the worldwide pandemic proved the need for a biosecurity program, therefore making this study significant. The study utilized the qualitative research design, where ten participants from different professions and runs of life were surveyed and interviewed. Various online platforms like Messenger and Google forms, as well as a one-on-one individual depth interview, were conducted and used to gather the information needed. The findings are presented as follows: in terms of awareness, a community needs to be educated and knowledgeable about biosecurity; in terms of leadership and practice and implementation, to have success in biosecurity in the municipality, there must be a reliable leadership and strict implementation of ordinances; and in terms of behavior, it has a big role on strengthening biosecurity in Kalamansig. This study concluded that a biosecurity program is essential, and needs more attention in the Philippines. This study is beneficial to society in the present age and in the years to come as it aims to strengthen society’s human biosecurity and protect the health and well-being of every individual.